Regulation of CaMKII signaling in cardiovascular disease - Kronlage, Mariya; Katus, Hugo; Backs, Johannes (Frontiers in pharmacology, 2015)
Heart failure (HF) is a major cause of death in the developed countries (Murray and Lopez, 1996; Koitabashi and Kass, 2012). Adverse cardiac remodeling that precedes heart muscle dysfunction is characterized by a myriad of molecular changes affecting the cardiomyocyte. Among these, alterations in protein kinase pathways play often an important mediator role since they link upstream pathologic stress signaling with downstream regulatory programs and thus affect both the structural and functional integrity of the heart muscle. In the context of cardiac disease, a profound understanding for the overriding mechanisms that regulate protein kinase activity (protein-protein interactions, post-translational modifications, or targeting via anchoring proteins) is crucial for the development of specific and effective pharmacological treatment strategies targeting the failing myocardium. In this review, we focus on several mechanisms of upstream regulation of Ca(2+)-calmodulin-dependent protein kinase II that play a relevant pathophysiological role in the development and progression of cardiovascular disease; precise targeting of these mechanisms might therefore represent novel and promising tools for prevention and treatment of HF.
Gesehen am 05.04.2018